Amorphous carbon based nanofluids for direct radiative absorption in solar thermal concentrators – Experimental and computational study. (January 2022) - Pramanik, Anurag; Singh, Harjit; Chandra, Ram; Vijay, Virendra Kumar; Suresh, S.
Abstract: Directly solar radiation absorbing nanofluids have the potential to absorb a wide spectrum of solar radiation and displace selectively coated metallic receivers in solar thermal collectors. Parameters including nanoparticle concentration, synthesis and storage conditions, can influence their long-term usage. In this study, 60 min was found to be optimal sonication duration to synthesise a uniform suspension of nanofluid containing amorphous-carbon nanoparticles and ethylene glycol as base fluid. Nanoparticle concentration can be used to tune extinction coefficient of nanofluid in the range of 75–400 m −1 for wavelength range of 320–1000 nm. Long-term stability and high temperature studies showed a time and temperature dependent increase in transmittance of nanofluid which is restored by 5 min of stirring. Computational modelling highlighted the role of incident intensity, nanoparticle concentration as well as inlet flow rate on receiver exit temperature. A ray-optics model employing weather data for Delhi (India) can predict the optical efficiency of an Asymmetric Compound Parabolic Concentrator solar collector. This combined approach can enable to predict the flow rate required to achieve a desired supply temperature at target locations. This rational framework combining experimental and computational approaches can be used to identify design parameters relevant for application of nanofluids in thermal collectors. HIGHLIGHTS: Synthesis parameters for nanofluids containing amorphous carbon in ethylene glycol. Nanofluid optical properties can be tuned by changing nanoparticle concentration. Temperature and time dependent settling can be restored by 5 min of stirring. Extinction coefficient of nanofluid varies linearly with nanoparticle concentration. Performance of concentrating solar collectors using directly absorbing nanofluid.